Awareness of Small and Medium Enterprises on Competition Act 2010 and Malaysian Competition Commission - Hasnah, Haron; Ishak, Ismail; Yuvaraj, Ganesan; Gautama, Idris (2018)
The Competition Act 2010 (CA 2010) was gazetted on June 2010 and came into force on 1 January 2012. The Act is administered by the Malaysian Competition Commission (MyCC) which was established under the Competition Commission Act 2010. MyCC plays a vital role in ensuring the CA 2010 is well received. MyCC continuously embark in providing and engaging stakeholders across all levels with its advocacy and outreach activities. Therefore, the objectives of this research are to examine the awareness level of Small and Medium Enterprise (SMEs) and their knowledge of the CA2010 and of the role of MyCC. In addition, further analysis the level of awareness of SMEs by state, market structures and sectors and also compared with Baseline study which conducted in year 2013. A total of 154 respondents involved in this study and the results show that increased in SMEs awareness and knowledge about the MyCC and CA2010. Furthermore, the results showed most of states were aware of the existence of MyCC and CA2010. Meanwhile, in term of market structures, the export-oriented businesses have higher level of awareness of compared than the domestic-driven businesses. The study will benefit the relevant authority to strategies the activities plan to enhance to their service quality and knowledge about the competition act.